1975
DOI: 10.1037/h0076655
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences and autonomic control: Absorption, hypnotic susceptibility, and the unilateral control of skin temperature.

Abstract: We proposed to (a) replicate earlier findings that human subjects could voluntarily control peripheral skin temperature, (b) test the hypothesis that hyponotic susceptibility and the capacity for absorbed, imaginative attention will enhance autonomic learning and performance, and (c) demonstrate a learning effect, if one exists. We compared seven subjects who scored high with seven subjects who scored low on both a modified version of the Harvard Group Scale of Hypnotic Susceptibility and the Tellegen Absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…Surprisingly, the presumably superior feedback system did not improve the ability to self-regulate hand temperature (for a fuller METHODS IN THERMAL BIOFEEDBACK 619 discussion, see Taub, 1977). Roberts and co-workers (Roberts, Kewman, & Macdonald, 1973;Roberts, Schuler, Bacon, & Zimmerman, 1975) have employed auditory feedback and have obtained results similar to those of this laboratory.…”
Section: The Information Displaysupporting
confidence: 60%
“…Surprisingly, the presumably superior feedback system did not improve the ability to self-regulate hand temperature (for a fuller METHODS IN THERMAL BIOFEEDBACK 619 discussion, see Taub, 1977). Roberts and co-workers (Roberts, Kewman, & Macdonald, 1973;Roberts, Schuler, Bacon, & Zimmerman, 1975) have employed auditory feedback and have obtained results similar to those of this laboratory.…”
Section: The Information Displaysupporting
confidence: 60%
“…Tellegen and Atkinson (1974) reported correlations of .27 and .43 with two versions of the Group Scale of Hypnotic Susceptibility and .42 with Field's Hypnotic Depth Scale. Test-retest and split-half reliabilities over .80 have been reported for the TAS (Roberts, Schuler, Bacon, Zimmerman, & Patterson, 1975). Scoring of the TAS is from 0-34.…”
Section: Questionnairesmentioning
confidence: 99%
“…In their initial study Tellegen and Atkinson (1974) reported correlations of .27 and .42 (across two samples) between the TAS and hypnotizability as measured by the Harvard Group Scale of Hypnotic Susceptibility, Form A A;Shor & h e , 1962). The finding of a relation between hypnotizability and absorption has been replicated on numerous occasions (e.g., Crawford, 1982;Finke & MacDonald, 1978;Kihlstrom et al, 1980;Nadon, Hoyt, Register, & Kihlstrom, 1991;Nadon, Laurence, & Perry, 1987;Roberts, Schuler, Bacon, Zimmermann, & Patterson, 1975;see Roche & McConkey 1990, for a comprehensive review of the hypnotizability and absorption relation).…”
mentioning
confidence: 89%